Integration of Count Difference and Curve Similarity in Negative Regulatory Element Detection - He, Na; Wang, Wenjing; Fang, Chao; Tan, Yongjian; Li, Li; Hou, Chunhui (Frontiers in Genetics, 2022)
Negative regulatory elements (NREs) down-regulate gene expression by inhibiting the activities of promoters or enhancers. The repressing activity of NREs can be measured globally by Massively Parallel Reporter Assays (MPRAs). However, most existing algorithms are designed for the statistical detection of positively enriched signals in MPRA datasets. To identify reduced signals in MPRA experiments, we designed a NRE identification program, Fast-NR, by integrating the count and graphic features of sequenced reads to detect NREs using datasets generated by experiments of self-transcribing active regulatory region sequencing (STARR-seq). Fast-NR identified hundreds of silencers in human K562 cells that can be validated by independent methods.